Student mathematics engagement: development and validation of a measurement instrument. - Taiwo Omorinola Oladipo-Abodunwa; Joshua Oluwatoyin Adeleke (PhD); Musa Adekunle Ayanwale (PhD) (African Journal of Behavioural and Scale Development Research, 2019)
Engagement is an aspect of mathematics affective domain that previous studies had reported could influence learning of the subject. However, most of the tools available to measure this construct were validated using obsolete psychometric methods. This study therefore adopted a survey research design to develop Student Mathematics Engagement Scale (SMES). The sample consisted of four thousand, one hundred and forty-six (4,146) SS3 examinees from 73 schools randomly selected from co-educational public secondary schools in Oyo State, Nigeria. Data were analysed using Exploratory Factor Analysis (EFA), Horn Parallel Analysis (HPA), Confirmatory Factor Analysis (CFA) and Ordinal Alpha Reliability Coefficient. The results showed that the scale was reduced from thirty-three (33) to sixteen (16) items across three (3) components. Final compliance indices were: χ2 = 658.99, p = 0.10, RMSEA= 0.04, GFI = 0.98, AGFI = 0.97, TLI = 0.94, NFI = 0.94, SRMR= 0.01, CFI= 0.95 and IFI= 0.95. The ordinal alpha reliability index of the three (3) factors of SMES was 0.87, while the reliability index of each of the subscales of the SMES ranged from 0.76 to 0.87. Mathematics teachers at secondary schools should be encouraged to use the scale for measuring students' level of engagement in mathematics.